(untitled) (Journal of Dhaka National Medical College & Hospital, 2018)
Bardet Biedl syndrome is a rare heterogeneous autosomal recessive disorder. A very few case was reported in Bangladesh. Here we two cases will be discuss .One is a 18 years young boy presented with childhood obesity (>97%), polydactyly in all 4 limbs, bilateral gynaecomastia, acanthosis nigricans, night blindness, mental retardation. After evaluation he was found to have hypogonadotrophic hypogonadism, primary hypothyroidism, dislipidaemia, renal impairment, elevated liver enzymes and retinitis pigmentosa. We advised him to reduce weight and implemented with weight reducing diet. Levothyroxine and Metformin were started. And another case is a 38 years unmarried lady presented with overweight, polydactyly in lower limbs, blindness, paraparesis and mental retardation with known Diabetes mellitus and hypertension. After evaluation she was found to normal hormonal activity and retinitis pigmentosa. She was also treated with anti- diabetic (Insulin) and antihypertensive medication. Both cases were scheduled for check-up every 2-3 months both in endocrinology and eye OPD. J. Dhaka National Med. Coll. Hos. 2018; 24 (02): 47-49